2012
DOI: 10.1242/dev.071456
|View full text |Cite
|
Sign up to set email alerts
|

RIPPLY3 is a retinoic acid-inducible repressor required for setting the borders of the pre-placodal ectoderm

Abstract: SUMMARYRetinoic acid signaling is a major component of the neural posteriorizing process in vertebrate development. Here, we identify a new role for the retinoic acid receptor (RAR) in the anterior of the embryo, where RAR regulates Fgf8 expression and formation of the pre-placodal ectoderm (PPE). RAR2 signaling induces key pre-placodal genes and establishes the posterolateral borders of the PPE. RAR signaling upregulates two important genes, Tbx1 and Ripply3, during early PPE development. In the absence of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 105 publications
0
84
0
Order By: Relevance
“…We found that overexpression of Ripply2 double mutants (WRPW→AAAA; FPVQ→AAAA), which presumably cannot interact with Tbx or Groucho, are phenotypically normal in somite morphology, marked by Myod (Fig. S13D) We have previously shown that Ripply3 inhibits Tbx1 transcriptional activity in vivo (Janesick et al, 2012). Similarly, zebrafish Ripply1 converts Tbx6 from a transcriptional activator to a repressor in vitro (Kawamura et al, 2008) and this protein interaction is essential for establishing the posterior somite boundary (Morimoto et al, 2007;Takahashi et al, 2010).…”
Section: Ripply2 Regulates Somitogenesis Downstream Of Ra Via Grouchomentioning
confidence: 77%
See 4 more Smart Citations
“…We found that overexpression of Ripply2 double mutants (WRPW→AAAA; FPVQ→AAAA), which presumably cannot interact with Tbx or Groucho, are phenotypically normal in somite morphology, marked by Myod (Fig. S13D) We have previously shown that Ripply3 inhibits Tbx1 transcriptional activity in vivo (Janesick et al, 2012). Similarly, zebrafish Ripply1 converts Tbx6 from a transcriptional activator to a repressor in vitro (Kawamura et al, 2008) and this protein interaction is essential for establishing the posterior somite boundary (Morimoto et al, 2007;Takahashi et al, 2010).…”
Section: Ripply2 Regulates Somitogenesis Downstream Of Ra Via Grouchomentioning
confidence: 77%
“…RARα or RARγ knockdown in the frog, Xenopus laevis, produces specific defects in neuronal differentiation, pre-placodal ectoderm formation and axial elongation (Janesick et al, 2014(Janesick et al, , 2013(Janesick et al, , 2012Koide et al, 2001). We have shown that RARγ is required for axial elongation and for maintenance of the caudal progenitor pool (Janesick et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations